Don't believe your eyes! - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
Camogli is a small town in Italy. People there paint in a special style called'trompe l'oeil. These paintings are so goos, viewers think they're real items, but they're not. They're paintings. What things are real in Camogli and what things are actually paintings.
Title from title screen
Video and audio on DVD
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography